Evaluación de granos secos solubles de maíz en el alimento sobre parámetros de salud y productivos de pollos COBB 500 - Macías Zambrano, José Manuel (2022)
The objective of this research was to evaluate the inclusion of dry soluble corn grains (DDGS) in the diet of Cobb 500 chickens on health and production parameters. 300 birds were used, which were assigned to a Completely Random Design, with 4 treatments (T1: Control treatment; T2: Inclusion of 10% DDGS; T3: Inclusion of 15% DDGS; T4: Inclusion of 20% DDGS ) and 3 repetitions per treatment. The data was analyzed through an analysis of variance, using the Tukey test at 5% with the statistical package InfoStat (2018). In the evaluation of the productive variables, significant differences were found (p<0.05), in which the T4 chickens achieved a higher weekly weight (2455.33g) and accumulated weekly weight gain (503.40g); the highest efficiency in feed conversion (1.57). In addition, higher percentages were found in carcass yield (84.37%); viability (96%). No significant differences were found between the treatments (p˃0.05) on the variable hematological parameters. It is concluded that the feeding of Cobb 500 broilers with the inclusion of DDGS at 20% can be used to improve the productive performance of Cobb 500 chickens without affecting health.